Use of nuclear power plant released tritium as a groundwater tracer (Rudarsko-geološko-naftni zbornik, 2019)
Tritium presents a natural radioactive isotope which can be used as a tracer in hydrology. This paper presents the usage of tritium in hydrogeological research of the Zagreb aquifer, which presents the country`s strategic water reserves and is protected by the Republic of Croatia. In the research area, higher tritium content in surface water and groundwater is the result of releasing coolant water from the Nuclear power plant Krško. Tritium content was measured in 13 piezometers and one pumping well, in the wider area of the Petruševec and Kosnica well fields. It has been shown that tritium from cooling water is much more pronounced than its natural seasonal variability, and it can be very useful as a tracer. Also, results showed that the intensity and delay of responses in the aquifer depend on their distance from the Sava River and piezometer depth. Furthermore, the results suggest that variable hydrologic conditions can generate rapid change in the groundwater flow direction and affect tritium transport through the aquifer.